Propuesta de intervención arquitectónica en las termas Kunugyaku, en la comunidad 10 de Octubre. (Pilahuin, Tungurahua, Ecuador) - Pérez Ayala, Evelyn Sarahi (2024)
The Kunugyaku architectural design proposal is located in the parish of Pilahuin, Ambato canton, Tungurahua Province in Ecuador. Pilahuin is the rural parish with the highest poverty rate in Ambato, despite this it is characterized by its vast natural wealth, as is the case of the Kunugyaku geothermal resource, which is currently presented as a rudimentary place built according to the economic availability of the community 10 de Octubre. This research work seeks to take advantage of the existing thermal resource, through an architectural proposal that implements spaces to generate and enhance the economic activity of the Kunugyaku complex, as well as develop spaces for relaxation and enjoyment of the crystalline waters, which are favored by a natural environment of high mountains with an altitude of approximately 3670 m above sea level. The project starts with conceptual research, which precedes the diagnosis of the place until reaching the architectural proposal, which focuses on encouraging tourism to promote economic activity in the sector.